ImmunoPET imaging of Trop2 expression in triple-negative breast cancer using [64Cu]Cu-NOTA-Trodelvy-F(ab')2. - Huang, Wenpeng; Zhang, Yuwei; Xiao, Xiaoyan; Yang, Qi; Mixdorf, Jason C.; Sun, Xinyao; Engle, Jonathan W.; Fan, Yu; Li, Liming; Kang, Lei; Cai, Weibo (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Purpose: The Trop2-targeting antibody-drug conjugate (ADC) sacituzumab govitecan (Trodelvy) has demonstrated remarkable efficacy in patients with metastatic triple-negative breast cancer (TNBC). ImmunoPET imaging offers a noninvasive method to visualize the expression and distribution of target antigens in vivo. In this study, we developed F(ab')2 fragments of Trodelvy for immunoPET imaging to detect Trop2 expression in TNBC models, aiming to achieve a shorter imaging window. Materials and methods: Trodelvy-F(ab')2 was prepared using the IdeS protease kit and purified with Magne Protein A beads and MagneHis™ Ni Particles. The products were characterized by non-reducing sodium dodecyl sulfate-polyacrylamide gel electrophoresis and high-performance liquid chromatography. Trodelvy-F(ab')2 was subsequently conjugated with p-SCN-Bn-NOTA (NOTA) for radiolabeling with 64Cu. ImmunoPET imaging using [64Cu]Cu-NOTA-Trodelvy-F(ab')2 was conducted at multiple time points to assess its in vivo targeting capability. Immunohistochemical and immunofluorescence analyses were performed on tumor tissues obtained from tumor-bearing mice. Results: The radiochemical yield of [64Cu]Cu-NOTA-Trodelvy-F(ab')2 exceeded 90%, with a radiochemical purity greater than 99%. High Trop2 expression was observed in MDA-MB-468 cells, whereas MDST8 cells exhibited low expression. The apparent dissociation constant (KD) of [64Cu]Cu-NOTA-Trodelvy-F(ab')2 for MDA-MB-468 cells was determined to be 14.60 nM. ImmunoPET imaging revealed clear uptake of [64Cu]Cu-NOTA-Trodelvy-F(ab')2 in MDA-MB-468 tumors as early as 4 h post-injection (p.i.) (8.20 ± 0.98%ID/g), peaking at 12 h p.i. (11.13 ± 0.45%ID/g). Uptake was significantly higher compared to the MDST8 group (3.37 ± 0.45%ID/g at 4 h; 5.77 ± 0.74%ID/g at 12 h) and the blocking group (2.67 ± 0.21%ID/g at 4 h; 3.07 ± 0.37%ID/g at 12 h). [64Cu]Cu-NOTA-Trodelvy-F(ab')2 achieved significantly higher tumor-to-heart ratios in MDA-MB-468 tumors (3.87 ± 0.58 vs. 0.74 ± 0.19, P = 0.0019) at 12 h p.i., compared to [64Cu]Cu-NOTA-Trodelvy, indicating superior tumor contrast. Conclusions: Our findings indicate that [64Cu]Cu-NOTA-Trodelvy-F(ab')2 exhibits rapid, specific, and sustained tumor accumulation in TNBC models, enabling precise and noninvasive monitoring of Trop2 expression.